GLOBAL COMPETITIVENESS OF THE EUROPEAN UNION MEMBER STATES: EVOLUTION AND PERSPECTIVES - Tudose, Mihaela Brindusa; Rusu, Valentina Diana (Studies and Scientific Researches. Economics Edition, 2015)
Our paper is analyzing the theoretical and empirical research in the field of competitiveness and it presents the methodology of determining the global competitiveness index. Also, our paper is analyzing the evolution of the global competitiveness index in the Member States of the European Union, in the last years. The results obtained show that more than half of European Union Member States recorded an increase in the global competitiveness index on the account of the basic influence factors. With the exception of six countries (Bulgaria, Cyprus, Croatia, France, Italy, Malta), the European Union countries show a favorable influence of the efficiency on the index of global competitiveness. The highest contribution of the efficiency on the increase of global competitiveness is recorded in Portugal, Romania, Latvia, Lithuania and Bulgaria; on the opposite side is Malta, Cyprus and Germany. Regarding the influence of innovation, only three countries have recorded a negative impact of the innovation on the global competitiveness index: Finland, Spain and Austria. On the other hand Romania, Cyprus and Portugal show the highest favorable effect of innovation on the competitiveness.